Pemetaan Potensi Pelaku Informal (Bengkel) Sepeda Motor Listrik yang Bersedia Melakukan Daur Ulang Limbah Baterai - Annie Purwani; Ichsanul Fikri Umar Irawan; Iqbal Ramadhan (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Batteries are the primary component in electric motorcycle propulsion systems, playing a crucial role in storing and supplying energy. However, batteries have a limited lifespan, potentially becoming waste after their useful life. Battery waste is categorized as hazardous and toxic waste (B3) because it contains heavy metals and chemical compounds that can negatively impact human health and the environment if not managed properly. As the adoption of electric motorcycles increases in Indonesia, particularly in the Special Region of Yogyakarta (DIY), the issue of battery waste management is becoming increasingly important. Currently, there are no electric motorcycle manufacturers openly willing to manage post-life battery waste, particularly through recycling activities. This situation creates a gap that informal actors could potentially exploit. Informal actors often possess flexibility and basic technical skills, but their capacity to manage battery waste safely and sustainably still needs to be mapped and strengthened. This study focused on mapping the potential capabilities of informal actors in the Special Region of Yogyakarta by 2025. The results indicate that the potential for informal actors capable of providing battery repair services is only around 1%. This figure is very small and therefore insufficient to support future battery waste management needs. Therefore, multi-stakeholder support is needed, from the government and manufacturers to the community, to encourage capacity building among informal actors. This effort is crucial to anticipate the success of the government's 2030 target for electric vehicle conversion, while also ensuring environmental sustainability.